Neutrophils: Musketeers against immunotherapy - Zahid, Kashif Rafiq; Raza, Umar; Tumbath, Soumya; Jiang, Lingxiang; Xu, Wenjuan; Huang, Xiumei (Frontiers in Oncology, 2022)
Neutrophils, the most copious leukocytes in human blood, play critical role in tumorigenesis, cancer progression and immune suppression. Recently, neutrophils have attracted attention of researchers, immunologists and oncologists because of their potential role in orchestrating immune evasion in human diseases including cancer which has led to a hot debate redefining the contribution of neutrophils in tumor progression and immunity. To make this debate fruitful, this review seeks to provide recent update about contribution of neutrophils in immune suppression and tumor progression. Here, we have first described the molecular pathways through which neutrophils aid in cancer progression and orchestrate immune suppression/evasion. Later, we have summarized the underlying molecular mechanism of neutrophils-mediated therapy resistance and have highlighted various approaches through which neutrophils antagonism may heighten the efficacy of the immune checkpoints blockade therapy. Finally, we have highlighted several unsolved questions and hope that answering these questions will provide a new avenue towards immunotherapy revolution.